2013
DOI: 10.1371/journal.pone.0069183
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory CD4+Foxp3+ T Cells Control the Severity of Anaphylaxis

Abstract: ObjectiveAnaphylaxis is a life-threatening outcome of immediate-type hypersensitivity to allergen, consecutive to mast cell degranulation by allergen-specific IgE. Regulatory T cells (Treg) can control allergic sensitization and mast cell degranulation, yet their clinical benefit on anaphylactic symptoms is poorly documented. Here we investigated whether Treg action during the effector arm of the allergic response alleviates anaphylaxis.MethodsWe used a validated model of IgE-mediated passive systemic anaphyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
5
20
1
Order By: Relevance
“…The regulatory T‐cell related cytokine IL10 reduced the release of cytokines in rat peritoneal mast cells and mast cell degranulation in in vivo models . Recently, it has been shown that constitutive Foxp3+ regulatory T‐cells can control mast cell activation and IgE‐dependent anaphylaxis in mice . These findings support the finding that cross‐talk between mast cells and T‐cell subsets and thereby a change in cytokine profiles underlie the reduction in anaphylactic shock symptoms, acute skin response and mast cell degranulation.…”
Section: Discussionsupporting
confidence: 69%
“…The regulatory T‐cell related cytokine IL10 reduced the release of cytokines in rat peritoneal mast cells and mast cell degranulation in in vivo models . Recently, it has been shown that constitutive Foxp3+ regulatory T‐cells can control mast cell activation and IgE‐dependent anaphylaxis in mice . These findings support the finding that cross‐talk between mast cells and T‐cell subsets and thereby a change in cytokine profiles underlie the reduction in anaphylactic shock symptoms, acute skin response and mast cell degranulation.…”
Section: Discussionsupporting
confidence: 69%
“…Similar effects of Tregs on mast cells have been shown in other experimental models of anaphylaxis 230,231 and contact hypersensitivity. 232…”
Section: Ntregs Attenuate Mast Cell-dependent Lung Allergic Responsessupporting
confidence: 79%
“…Degranulation of mast cells was decreased in cells co‐cultured with nTregs but not with naive CD4 + CD25 − T cells. Similar effects of Tregs on mast cells have been shown in other experimental models of anaphylaxis and contact hypersensitivity …”
Section: Cd4+ Tregs Modulate Lung Allergic Responsessupporting
confidence: 78%
“…Interestingly, Tregs express very high levels of GITR and OX40, but not 4-1BB; this expression pattern may explain the more potent antibody responses caused by agonizing GITR and OX40, especially in light of recent findings that Tregs are involved in control of the germinal center response and that depletion of Tregs can enhance anaphylaxis. [57][58][59][60][61][62][63] An important question is whether anaphylaxis caused by repetitive intraperitoneal dosing of DTA-1 and OX86 in mice is translatable to humans treated with humanized versions of these antibodies. Our preclinical observations will heighten awareness that anaphylaxis may be of particular concern when using antibodies targeting GITR and OX40.…”
Section: Discussionmentioning
confidence: 99%